PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU MELALUI VIDEO DALAM MANAJEMEN DIARE PADA BALITA DI DESA SINGGULING WILAYAH KERJA PUSKESMAS LUBUK ALUNG TAHUN 2025 - Valentine, Hega; Wati, Henny; Nelly, Septa; Rahmi, Rahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Diarrhea is an infectious disease that causes death in infants and toddlers. The high rate of diarrhea in toddlers is due to the lack of anticipation in the management of diarrhea, low education and ignorance of mothers treating diarrhea. This study aims to determine the effect of health education on mother's knowledge in the management of diarrhea in toddlers in Singguling Village, Working Area of the Lubuk Alung Health Center in 2025. Health education through video is one of the media to improve toddlers. This research was conducted on May 20, 2025. The type of research used was Quasy Experiment design with one group pretest and posttest design. design. The sample of this research is mothers who have toddlers totaling 20 people. Data processing using computerization with the Wilcoxon test. The results showed that the average knowledge of mothers in managing diarrhea in infants before being given health education (pretest) was low. While the average knowledge of mothers after being given health education (posttest) was high, the results of the statistical test obtained a p value (0.000) <0.05. The conclusion of this study is that there is an effect of providing health education on mother's knowledge in managing diarrhea in toddlers in the Lubuk Alung Working Area. It is hoped that health workers can improve services in providing information using video media to mothers who have children under five in diarrhea management.Keywords : Diarrhea Management, Health Education, Mother, Toddler.